Real‐Time Heat Transfer Model Based on Distributed Thermophysical Property Calculation for the Continuous Casting Process. Issue 5 (11th December 2018) - Ji, Cheng; Deng, Shimin; Guan, Rui; Zhu, Miaoyong
Abstract : In this work, a one‐dimensional real‐time heat transfer model, which considers the effect of varying thermophysical properties along slab thickness direction caused by the distribution of solute segregation, is built to predict the location of the solidification end of a wide‐thick continuous casting slab accurately. According to the measurement results of carbon segregation on the slab transverse section, a database of thermophysical properties with different carbon contents is established based on the micro‐segregation model. At the beginning of the calculation, the pre‐calculated thermophysical properties of the target slab are pre‐loaded to random access memory (RAM), and the corresponding physical parameter data are called from RAM to complete the calculation process according to the pre‐measured carbon concentration at different slab thicknesses. Additionally, the solidification relationship between the slab center and other positions along the width direction is derived based on an offline two‐dimensional heat transfer model. With calling the relationship, the whole slab uneven solidification process can be described based on the real‐time calculated results of the slab centerline solidification process. The real‐time heat transfer model is validated by measuring the slab thickness and surface temperature. Abstract : In this work, a one‐dimensional real‐time heat transfer model, which considers the effect of varying thermophysical properties along slab thickness direction caused by the distribution of solute segregation, is built to predict the location of the solidification end of a wide‐thick continuous casting slab accurately.